Plant Tissue Culture Techniques and Experiments - Smith, Roberta H. (Academic Press, 2000)
Provides laboratory exercises in plant tissue culture that demonstrate major educational concepts. This book covers tissue culture laboratory setup, supplies, media, and explant preparation, and measurements. It includes supplementary sections and scheduling and interrelationships of exercises suitable for teachers.